Health policies in central and South Eastern Europe: challenges and chances (Italian Journal of Public Health, 2009)
Background: Fundamental political changes in Central and South Eastern Europe in the aftermath of the fallof the iron curtain enter a new phase after accession of some countries to the EU.Methods: The article reviews and analyses current regional and international developments and factors,which are influential for health policies in the region. Special attention is given to collaboration – both oftechnical and of political nature – within the region and with international organizations and donors. Theresponse to international health policy frameworks and the impact of international health strategies is beinganalysed.Results: The results point towards common political and structural features in the countries of the region.Regional networks seem to be a very promising structure for health policy development. Despite the politicalwill, health care reforms still don’t show the expected results. The partnership with the EU is the mostinfluential one.Conclusions: Regional networks need to be transformed into regionally owned structures. It seems to becrucial to tackle informal parallel systems and to increase responsibility for health professionals. The need forreforms and the prospect of neighbouring and joining the EU create a unique momentum to develop ownhealth policies without international interference.
Keywords: Europe; Easter; health policy; European Union; international cooperation; public health